Dermal Tattoo Biosensors for Colorimetric Metabolite Detection. Issue 31 (3rd July 2019) - Yetisen, Ali K.; Moreddu, Rosalia; Seifi, Sarah; Jiang, Nan; Vega, Katia; Dong, Xingchen; Dong, Jie; Butt, Haider; Jakobi, Martin; Elsner, Martin; Koch, Alexander W.
Abstract: Tattooing is a ubiquitous body modification involving the injection of ink and/or dye pigments into the dermis. Biosensors in the form of tattoos can be used to monitor metabolites in interstitial fluid. Here, minimally invasive, injectable dermal biosensors were developed for measuring pH, glucose, and albumin concentrations. The dermal pH sensor was based on methyl red, bromothymol blue, and phenolphthalein, which responded to a pH range from 5.0 to 9.0. The dermal glucose sensor consisted of glucose oxidase, 3, 3′, 5, 5′‐tetramethylbenzidine, and peroxidase that detected concentrations up to 50.0 mmol L −1 . The dermal albumin sensor consisted of 3′, 3′′, 5′, 5′′‐tetrachlorophenol‐3, 4, 5, 6‐tetrabromosulfophthalein to measure concentrations up to 5.0 g L −1 . The sensors were multiplexed in ex vivo skin tissue and quantitative readouts were obtained using a smartphone camera. These sensors can be used to manage of acid–base homeostasis, diabetes, and liver failure in point‐of‐care settings. Abstract : Colorimetric dermal sensors in the form of tattoos have been developed to measure pH, glucose, and albumin concentrations in an ex vivo porcine skin tissue model. The dermal sensors were injected into the dermis in an array format for multiplexed detection. Quantitative readouts were obtained with a smartphone camera.